Pengembangan Media Pembelajaran Berbasis Arduino Pada Mata Kuliah STEM - Adi Pramuda; Dwi Fajar Saputri; Matsun Matsun; Soka Hadiati (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
The industrial revolution 4.0 demands the integration of technology into the learning process so that STEM courses require technology-based media. This study aims to develop Arduino-based learning media in STEM courses. The specific objectives of this study are to determine; 1) the validity of Arduino-based learning media in STEM courses; 2) the practicality of Arduino-based learning media in STEM courses. The method used in this study is the research and development method with a 4D design. The research subjects consisted of development subjects, namely material experts and media experts, while the trial subjects were students of the Physics Education study program at IKIP PGRI Pontianak Semester IV who took STEM courses. Data collection tools were in the form of validation sheets and response questionnaires to measure the practicality of the developed media. Data analysis techniques used percentages with predetermined feasibility and practicality criteria. The results of the study showed that Arduino-based learning media had met the feasibility criteria with a High category, Arduino-based learning media was practical to use based on student assessments with a high category, and students gave a good response to Arduino-based learning media.